(untitled) (Jurnal Bahasa, 2022)
Deaf people communicate differently from those with normal hearing. Those who can hear communicate via speech whereas the deaf communicate through sign language. Their mode of communication is related to their inability to hear sounds due to their defective sense of hearing. They are thus labelled as disabled people. Recently, a new opinion has emerged that the deaf should be considered a linguistic minority. This opinion derives from the linguistic perspective, while from a medical point of view, the deaf are considered to be hearingimpaired. This issue will be examined based on the following research questions: (1) Are the deaf a disabled community or a language minority group? (2) What is the status of the deaf community in Malaysia? (3) What is the definition of communication and how do the deaf communicate? An understanding of these issues is important in order to make a comparison as well as to identify the differences and relationship between the modes of communication used by those with normal hearing and the deaf, and will provide information as to whether the deaf should be labelled as disabled persons devoid of language.